Hybrid cross-linked hydrogels based on fibrous protein/block copolymers and layered silicate nanoparticles: tunable thermosensitivity, biodegradability and mechanical durability. Issue 67 (30th June 2016) - Eslahi, Niloofar; Simchi, Abdolreza; Mehrjoo, Morteza; Shokrgozar, Mohammad Ali; Bonakdar, Shahin
Abstract : Schematic representation of LAPONITE® reinforced pluronic/chitosan/keratin nanocomposite hydrogel crosslinked with Genipin. Abstract : Stimuli responsive polymer hydrogels have sparked a considerable interest for biomedical applications. In this work, we present a novel injectable thermal responsive hydrogel based on mineral nanoclay (LAPONITE®), wool-derived fibrous protein (keratin), triblock copolymer (Pluronic), and chitosan biopolymer with potential applications for articular cartilage tissue engineering. Genipin was utilized as a natural crosslinker. The formation of polymer conjugates between the components is confirmed by FTIR and 1 H NMR spectroscopy. The nanocomposite hydrogel contains interconnected pores within the hydrogel network and the size of the pores is found to reduce at higher crosslinking density and on incorporation of LAPONITE® up to 6 wt%. A decrease in the swelling ratio and biodegradation after chemical crosslinking with genipin and addition of nanoclay is also observed. The ability of the hydrogels to undergo in situ crosslinking and rapid gelation under physiological conditions is shown. Evaluation of the viscoelastic properties of the hydrogels in simulated physiological conditions, i.e. elastic modulus ( G ′) and viscous modulus ( G ′′), indicates a significant enhancement of the properties through incorporation of the nanoclay mineral, which could be as high as 6 fold depending on the LAPONITE® concentration. To examine the in vitro cytotoxicity of the hydrogels for biomedical applications, an MTT assay using chondrocyte cells was performed. The cell attachment and viability were assessed as well. It can be concluded that the developed hydrogels are biocompatible (>90%) with good cell adhesion depending on their formulation and microstructure. The superior physico-mechanical properties of the hydrogels along with their cytocompatibility and the ability to encapsulate live cells at physiological conditions suggest that they have a high capacity to be used as cartilage scaffolds.